Peran Dewan Direksi Dalam Meningkatkan Reputasi Perusahaan (Studi Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia) - Jao, Robert; Yono, Benhard (Patria Artha Journal of Accounting dan Financial Reporting, 2020)
The purpose of this research is to examine the effect of the board of directors on corporate reputation. The population used is all manufacturing companies listed on the Indonesia Stock Exchange (IDX). . The sample selection using the purposive sampling method resulted in 32 companies or 128 observations. This study used secondary data, i.e. the number of boards of directors and corporate image index for companies included in Indonesia's Most Admired Company. The analytical method used is regression analysis. The result of analysis shows the size of the board of directors has a positive and significant influence on the company's reputation.